Community Nurses' Strategies for Overcoming Stunting Through a Family Approach - Ari Setiawati; Fransisca B. Batticaca; Evi Nurmaisa Biduri; Mery Kana; Maria Kurni Menga (LPPM Politeknik Sandi Karsa, South Sulawesi, Indonesia, 2025)
Introduction: Stunting is a high public health problem in Indonesia, especially in rural areas. This condition has a long-term impact on a child's physical growth, cognitive development, and quality of life. Community nurses are important in stunting prevention and management efforts, particularly through a more holistic and sustainable family-based approach. Research Objectives: To identify and analyze the strategies used by community nurses in tackling stunting through a family approach, as well as to understand the challenges faced in implementing these strategies at the community level. Research Methodology: This study uses a descriptive qualitative design with a phenomenological study approach. A total of 10 community nurses in areas with high stunting prevalence were interviewed in depth. Purposive sampling techniques were used to select participants, and data were analyzed using thematic methods to identify the main strategies applied in the family approach. Result: The results of the study showed that community nurses implemented several main strategies, namely: (1) health education to families about nutrition, sanitation, and child care, (2) regular home visits to monitor family growth and development, (3) collaboration with cadres and community leaders in the implementation of programs, and (4) empowerment of mothers through mentoring and counseling groups. Nurses also emphasize the importance of building trust with family to encourage behavior change. Obstacles include low family awareness, a local culture that conflicts with healthy practices, and limited resources. Conclusion: Strategies carried out by community nurses through a family approach have proven to be effective in efforts to overcome stunting. Family empowerment and cross-sector collaboration are key to success. Ongoing support is needed to strengthen the capacity of community nurses to carry out these roles optimally.